Новые виды пресноводных моллюсков (Bivalvia, Cycladidae) - Стадниченко, А.П. (Вестник зоологии, 1983)
The Euglesa solodovnikovi snail is elongated-oval, moderately convex, thin-walled. The convexity-height ratio of the snail is 0.59, the convexity-length one — 0.47. The most remote point from the valve closing plane is at a half of the valve height. The E. eichwaldi snail is oval, shallow-convex, thin-walled. The convexity-height ratio of the snail is 0.57, the convexity-length one — 0.43. The most remote point from the Valve closing plane is at the level somewhat exceeding a half of the snail height (from ihe lower edge of the snail).